PENERAPAN METODE PREWITT, CANNY DAN SOBEL PADA PROSES DETEKSI TEPI CITRA - Polinus Laia (STMIK Budi Darma, 2018)
Edge detection is the first step to completing information in an image where the edges characterize object boundaries that are useful for the identification process. There are many methods of edge detection, but in this study, the methods taken are the Prewitt method, the CANNY method and the Sobel method to detect the edges of objects in digital images. This system applies all three methods to improve the appearance of the boundary line of an object. This study discusses how to apply the three methods in the application Matlab 7.1. The purpose and benefits of this application are to recognize the application of the results of edge detection and obtain initial information about the edge detection features for object recognition for future researchers.